Anthropomorphism in Islamic Theology - Aditoni, Agus (Proceedings of International Conference on Islamic Civilization and Humanities, 2023)
This article aims to reveal the Anthropomorphic verses in the Qur'an. The Qur'an, which was revealed in Arabic to Muhammad (pbuh), contains clear teachings of the faith. This description of Allah's oneness and having no partners is mentioned repeatedly in the Qur'an. However, the method of understanding these theological verses varies from one to another and has shifted with the presence of the Ahl al-Hadith group, who narrated the hadiths of the Prophet. There are several hadiths that give personification of God's attributes, such as having hands, feet, face, and so on.This study is library research using a descriptive-analytic method with a socio-linguistic approach. Anthropomorphic verses are analyzed using explanatory analysis, which is an analysis that aims to explain more than just describing the meaning of a text of Anthropomorphic verses.The research found an attitude of inaccuracy in understanding the language of the Qur'an and there was an extreme tendency to understand the textual meaning of Anthropomorphic verses as well as further explanation about the meaning of anthropomorphic verses contextually.